2018
DOI: 10.1042/bcj20170894
|View full text |Cite
|
Sign up to set email alerts
|

CGA-N12, a peptide derived from chromogranin A, promotes apoptosis of Candida tropicalis by attenuating mitochondrial functions

Abstract: CGA-N12 (the amino acid sequence from the 65th to the 76th residue of the N-terminus of chromagranin A) is an antifungal peptide derived from human chromogranin A (CGA). In our previous investigation, CGA-N12 was found to have specific anti-candidal activity, though the mechanism of action remained unclear. Here, we investigated the effects of CGA-N12 on mitochondria. We found that CGA-N12 induced an over-generation of intracellular reactive oxygen species and dissipation in mitochondrial membrane potential, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…Because ROS are associated with yeast apoptosis in many cases [80], it was interested in determining whether hep 25 induces C. albicans cell death via apoptosis. In the early phase of apoptosis, the opening of the permeability transition pore causes mitochondrial dysfunction, losses of ∆Ψm and releases of apoptogenic factors into the cytosol [81,82]. Moreover, metacaspases are involved in the apoptotic cascade [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…Because ROS are associated with yeast apoptosis in many cases [80], it was interested in determining whether hep 25 induces C. albicans cell death via apoptosis. In the early phase of apoptosis, the opening of the permeability transition pore causes mitochondrial dysfunction, losses of ∆Ψm and releases of apoptogenic factors into the cytosol [81,82]. Moreover, metacaspases are involved in the apoptotic cascade [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the antifungal peptide CGA-N12 affected the external morphology of Candida cells, reducing the visual thickness of the cell wall at the minimal inhibitory concentration. CGA-N12 is a nonmembrane-active antifungal peptide that can enter C. tropicalis cells without rupturing the plasma membrane [30]. The binding proteins of C. tropicalis cells targeting CGA-N12 were screened by affinity chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial pellets were fixed in 5% glutaraldehyde in 20 mmol/l PBS ( pH 7.0) overnight at 4°C. After being washed with PBS, the yeast pellets were fixed with 1% OsO4 in PBS for 2 h. They were then dehydrated by being washed in increasing concentrations (30,50,70, and 95%) of acetone (twice per concentration) for 10 min each and further dehydrated in absolute acetone with three washes at 10 min each. The samples were embedded in Epon 812.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we found that amino acid sequence from 65th to 76th residue of the N-terminus of CGA (CGA-N12), a more potent and stable derivative of CGA that corresponds to the N-terminal Ala55-Gln76 sequence, exhibits antagonistic activity against Candida species [10]. Our previous studies clarified that CGA-N12 induces mitochondrial depolarization, and cytochrome c (Cyt c) leakage, ultimately causing mitochondria-dependent apoptosis of C. tropicalis [11]. However, the mechanism by which CGA-N12 decreases mitochondrial potential is unclear.…”
Section: Introductionmentioning
confidence: 99%